Mitochondrial genome of a spontaneous multiple myeloma bone cancer model mouse C57BL/KaLwRij strain. (1st November 2016) - Liu, Zhi-Gang; Tang, Bing; Zeng, Yun; He, Ning; Wang, Zhi-Yong; Han, Hang; Wang, Lin; Wang, Tai-Zhe; Yu, Hua-Long; Xiong, Min
Abstract: We sequenced the complete mitochondrial genome of a multiple myeloma bone cancer model mouse C57BL/KaLwRij strain for the first time. The total length of the mitogenome was 16, 297 bp, with 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes. This mitochondrial genome sequence contains 127 SNPs compared with the house mouse reference sequence.